The role of product quality, promotion, conformity in increasing consumer loyalty - Sukaris Sukaris; Novita Tri Yulia (Universitas Muhammadiyah Gresik, 2021)
Currently, business competition is getting more competitive. Companies must act to improve and maintain product quality. Product quality is the ability of a product to meet customer needs and consumers. Product quality can be a company's mainstay so that its products are able to compete in its market segments with similar products. Quality will encourage consumers to establish close relationships with the company for a long time which in turn creates consumer loyalty. This study aims to determine the effect of product quality, promotion and conformity on consumer loyalty at the